Mechanisms and applications of adipose-derived stem cell-extracellular vesicles in the inflammation of wound healing - Jia, Qingyi; Zhao, Hanxing; Wang, Yixi; Cen, Ying; Zhang, Zhenyu (Frontiers in Immunology, 2023)
Wound healing is a sophisticated process consisting of serial phases with overlaps, including hemostasis, inflammation, proliferation, and remodeling. Inflammation response is an early response that plays a crucial role in eliminating microbes and clearing damaged cell debris. However, in some pathological circumstances, such as diabetes mellitus, ischemia, trauma, deep burn, etc., abnormal inflammation can cause impaired wound healing. Adipose-derived stem cells (ADSCs) belong to the mesenchymal stem cells (MSCs) family exhibiting prospective applications in tissue regeneration and dermatological repairs. ADSCs secreted extracellular vesicles (ADSC-EVs) mimic the functions of ADSCs without the concerns of cell survival, immune response, and ethical issues. Studies have revealed that ADSC-EVs can inhibit abnormal inflammation responses and accelerate wound healing through various mechanisms. Moreover, some studies explored modifications in the cargo components of ADSC-EVs to enhance their therapeutic efficacy. Given the increasing studies focusing on the potential of ADSC-EVs in wound healing, how they interfere different phases of this process have been investigated in pieces. In this review, we summarized all up-to-date evidence to map a clearer picture of the underneath mechanisms of ADSC-EVs in inflammation response. The applications of ADSC-EVs aiming at inflammation in the healing process were also reviewed to provide therapeutic strategies for future investigators.